2014
DOI: 10.2500/aap.2014.35.3791
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of reported penicillin allergy in an urban outpatient adult population

Abstract: Penicillin P enicillin allergy remains the most common drug allergy reported, with a prevalence of ϳ8 -12% depending on the specific population evaluated. 1-3Higher rates are noted in individuals receiving more health care, including female patients and with increasing age.2,3 Symptoms associated with reported penicillin allergy classically include rash and/or itching, nausea, vomiting, shortness of breath, and anaphylaxis. However, often reported symptoms are either classified as unknown or representative of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 21 publications
6
76
4
4
Order By: Relevance
“…[10,11] The absence of organized continuing medical education programs and problematic physician attitude are other problems that add to under reporting of the adverse drug reaction. [12] There was predominance of female sex for adverse drug reactions which was similar to a study conducted by Albin S et al 13 The mean age of patients was 38.37 years which was less as compared to another study conducted by Jakob E. Borch et al [14] Amoxicillin and clavulanic acid combination was the most common penicillin causing ADRs. But studies done by Sara et al and Trubiano et al showed amoxicillin alone as most common penicillin causing ADRs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[10,11] The absence of organized continuing medical education programs and problematic physician attitude are other problems that add to under reporting of the adverse drug reaction. [12] There was predominance of female sex for adverse drug reactions which was similar to a study conducted by Albin S et al 13 The mean age of patients was 38.37 years which was less as compared to another study conducted by Jakob E. Borch et al [14] Amoxicillin and clavulanic acid combination was the most common penicillin causing ADRs. But studies done by Sara et al and Trubiano et al showed amoxicillin alone as most common penicillin causing ADRs.…”
Section: Discussionsupporting
confidence: 59%
“…Most common system affected was dermatological which was in line with other studies. [13,14] This increased reporting of dermatological ADRs could be due to easy recognition of dermatological reactions than involving other organ systems. [17] Most of the reactions were of probable causality according to WHO criteria since drug rechallenge was not done in any of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of allergic drug reactions were similar for both LyP and pcALCL subsets (28% overall) with reactions to penicillin type drugs reported most often in both cohorts. When compared to the 11.46% frequency of penicillin reactions reported by Albin, [15] only the pcALCL cohort had a significantly higher allergy rate (P= 0.012).…”
Section: Resultsmentioning
confidence: 66%
“…Specifically the calculated rates for allergic rhinitis/hay fever, asthma and eczema were 38.2% (1139/2982), 10.32% (443/4291), and 7.21% (156/2163), respectively. For the prevalence of allergic reactions to penicillin or derivatives, we used the 11.46% (1348/11,761) frequency from Albin's survey [15]. IgE-t levels were compared against several published series of non-atopic controls [2, [16][17][18][19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…Albin and Argarwal [32] at Mount Sinai in New York reviewed the EHRs of 11 761 internal medicine clinic patients and noted that 1348 (11.5%) carried a history of penicillin allergy. They confirmed that penicillin allergy was more common in elderly female patients.…”
Section: Public Health Implications Clinical Outcomes and Other Pramentioning
confidence: 99%